Effect of soilless media and irrigation scheduling on nutrient uptake and production of drip irrigated cherry tomato grown in polybags - KAMBLE, NOAH; SHERRING, ARPAN (Journal of Soil and Water Conservation, 2025)
A study was conducted at Agriculture Research and Demonstration Centre, Netafim Irrigation, Aurangabad, Maharashtra during the March- July, 2022 to study the effect of soilless media and irrigation scheduling on nutrient uptake, yield and quality of cherry tomato grown in polybags. Two different soilless media i.e. cocopeat and vermicompost were used as the growing media and their combinations along with three levels of irrigations i.e. at 50, 75, and 100% of crop evapotranspiration (ETc) and two irrigation intervals (daily and on alternate day) using arrow drippers in three replications as the treatments of the study with the objectives of determining best soilless growing media and its impact on nutrient uptake, growth and fruit yield of cherry tomato. Standard package and practices of growing cherry tomato under drip irrigation was used during the study. Total of thirty-six treatment combinations were used during experimentation. The study revealed that irrigating cherry tomato at 50 percent ETc on daily basis grown in mixture of cocopeat and vermicompost soilless media in a ratio of 70:30 w/w resulted increased plant height by 36.8 %, increased number of fruits per plant by 39% and higher yield by 82.18 %. It was noticed that it has higher nutrient uptake of N (87.02 kg ha-1), P (41.78 kg ha-1) and K (56.46 kg ha-1) over the treatment of cocopeat alone, with irrigation at 50% ETc on alternate day basis. Based on the results, it was recommended that to enhance the growth and yield of drip irrigated cherry tomato, mixture of cocopeat and vermicompost in a ratio of 70:30 w/w shall be used as a soilless media, with irrigation at 50 % ETc on daily basis if grown in polybags under field conditions.